Evaluating the effectiveness of the implementation process of the inclusive education policy in two schools in the Kavango East Region in Namibia - Hausiku, Regina Nangura (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.